THE INFLUENCE OF THE PROJECT-BASED LEARNING (PJBL) LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN HISTORY SUBJECT AT SMA NEGERI 2 SUNGAI KERUH - Kurnia, Sisi; Zamhari, Ahmad; Suriadi, Aan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
The Learning Model is a conceptual framework that systematically arranges procedures for organizing learning experiences to achieve specific learning goals. It is also helpful as a guide for teachers in planning and implementing the learning process. Project Based Learning is a form of learning that uses projects or activities as media. This study aimed to determine whether or not the project-based Learning (PJBL) learning model influenced student learning outcomes in history subjects. This research method uses the Quantitative Experiment method and data collection techniques using observation data, test data, and documentation. Data analysis techniques use validation tests, reliability tests, homogeneity tests, normality tests, t-tests, and u-tests. Student learning outcomes Based on the hypothesis test from the independent sample test table above, the value of Sig. (2-tailed) is 0.000, and the significant level value a = 0.05; thus, 0.000 0.05 means HO is rejected and Ha is accepted. The Project-Based Learning Learning Model influences student learning outcomes in history subjects at SMA Negeri 2 Sungai Keruh.